Modeling and control for the mode transition of a novel tilt-wing UAV - Wang, Yongchao; Zhou, Yaoming; Lin, Chenghao (Aerospace science and technology, 2019)
This paper mainly presents a multibody dynamics model and a novel control method for the mode transition of a new-style distributed propulsion tilt-wing UAV. Base on the technology of tensor flight dynamics, a multibody attitude dynamics model formulated in an invariant tensor form is developed for the mode transition such that the dynamics induced by the relative movement of the moving parts (wings and rotors) with respect to the fuselage could be formulated explicitly in the model. The control system is decoupled into two parts, namely the position subsystem and the attitude subsystem subject to input perturbation and external aerodynamic disturbances. A novel finite time altitude tracking controller is designed for position subsystem in terms of the existence of the external disturbances and the perturbations acting on the inputs such that the tilt-wing UAV can converge and move along the desired altitude trajectory in a finite time. Besides, a RISE-based attitude tracking controller is developed to control the attitude subsystem, which guaranteeing robustness to the external disturbances. Numerical simulations are carried out to illustrate the performance of the proposed controllers.